Strategies for Herbal Knowledge Inheritance Through Non-Formal Education in Traditional Villages - Susie Perbawasari; Priyo Subekti; Yugih Setyanto (Jurnal Komunikasi, 2024)
In the current context of globalization, the process of passing on traditional knowledge, particularly in relation to medicinal plant applications, faces significant hurdles. Kampung Adat Dangiang, facing this challenge, has initiated the establishment of Sekolah Adat as a non-formal education initiative aimed at the conservation and transmission of cultural and traditional knowledge to the next generation. This research investigates Sekolah Adat in Kampung Dangiang as an institution that plays an important role in knowledge preservation, where traditional healing principles and ritualistic practices are passed on across generations. Qualitative methodology, specifically case studies, was adopted in this research, providing a more narrative and exploratory approach to data collection. Through direct interaction, observation of daily rituals, and literature review, the research gathered information enriched by snowball sampling techniques from informants. The results reveal Sekolah Adat as an entity steeped in traditional values, functioning not only as an educational institution but as a living repository of medicinal plant knowledge and ritual practices. The Sekolah Adat introduces a unique pedagogical approach, combining lectures, demonstrations and practical applications, which overall enriches the spiritual existence of learners. The program creates a synergy between traditional herbal wisdom, modern chemical principles, and deep inner healing techniques. Although this integration of tradition and modernity poses challenges, especially in the aspect of scientific validation of ancestral practices, a strong commitment to the efficacy of traditional medicine, supported by generations of knowledge and anecdotes, continues to overcome such obstacles. In conclusion, Sekolah Adat Dangiang stands as a testament to the resilience of traditions that are able to adapt elegantly amidst the changing modern world. It signifies the importance of local wisdom in keeping cultural heritage alive and relevant amidst fast-changing global dynamics.